Quantification of micotoxins in feedstuffs used in commercial poultry diets - Castro, Johnatan (2015)
The study aimed to quantify the presence of micotoxins ochratoxine A and toxin T-2 in two common feedstuffs used in poultry diets (yellow corn and soybean meal) from different origins. Samples received for analysis from 2007 to 2011 were included in the study: 139 samples of corn and 64 of soybean meal were analyzed for ochratoxine A and 193 samples of corn and 144 of soybean were analized for toxin T-2. Results showed 66.2 and 67.4% positive samples of maize to ochratoxine A and toxin T-2 respectively, and 71.9 y 88.9% positive samples of soybean for ochratoxine A and toxin T-2 respectively. None of the samples surpassed the accepted limits recommended by the European Commission (2006/576/EC).